Integrated strategies to accelerate the adoption of cycling for transportation. (April 2017) - Savan, Beth; Cohlmeyer, Emma; Ledsham, Trudy
Graphical abstract: Highlights: Social psychological behaviour change literature can be applied to cycling programs. We established an adaptable, evidenced-based strategy for cycling program developers. A mixed-method, multi-stage approach is essential for cycling adoption programs. Behaviour-based cycling promotion initiatives require further research attention. Abstract: This study synthesizes academic social psychological behaviour change literature with reports on the practical, community-based application of cycling programs. We identify the combination of psychological tools demonstrated to lead to changes in behaviour in the target population. We compare these tools with reports demonstrating evidence for success from monitored programs to encourage cycling adoption. Based on the alignment between these two literatures, we developed an adaptable, evidenced-based strategy for program developers to most effectively accelerate the adoption of cycling for transportation in areas where physical barriers are few. A brief case study affirms the effectiveness of this approach.